Unravelling the genetic background in individuals with Familial Hypercholesterolemia phenotype - Medeiros, A.M. (2021)
Aim: Genetic diagnosis is the only method to correctly identify patients with Familial hypercholesterolemia (FH) but 40%–50% of these individuals do not have a causative variant in LDLR, APOB and PCSK9 genes. In this work, we aim to characterize the genetic background of individuals with FH phenotype.